Electrochemical Detection of Electrolytes Using a Solid-State Ion-Selective Electrode of Single-Piece Type Membrane - Chen, Li-Da; Wang, Wei-Jhen; Wang, Gou-Jen (Biosensors (Basel), 2021)
This study aimed to develop simple electrochemical electrodes for the fast detection of chloride, sodium and potassium ions in human serum. A flat thin-film gold electrode was used as the detection electrode for chloride ions; a single-piece type membrane based solid-state ion-selective electrode (ISE), which was formed by covering a flat thin-film gold electrode with a mixture of 7,7,8,8-tetracyanoquinodimethane (TCNQ) and ion-selective membrane (ISM), was developed for sodium and potassium ions detection. Through cyclic voltammetry (CV) and square-wave voltammetry (SWV), the detection data can be obtained within two minutes. The linear detection ranges in the standard samples of chloride, sodium, and potassium ions were 25–200 mM, 50–200 mM, and 2–10 mM, with the average relative standard deviation (RSD) of 0.79%, 1.65%, and 0.47% and the average recovery rates of 101%, 100% and 96%, respectively. Interference experiments with Na+, K+, Cl−, Ca2+, and Mg2+ ions demonstrated that the proposed detection electrodes have good selectivity. Moreover, the proposed detection electrodes have characteristics such as the ability to be prepared under relatively simple process conditions, excellent detection sensitivity, and low RSD, and the detection linear range is suitable for the Cl−, Na+ and K+ concentrations in human serum.